Evaluation occupationally radiation exposure during diagnostic imaging examinations - Johary, Yehia H.; Albarakati, Sultan; Alsohaim, Abdullah; Aamry, Ali; Aamri, Hussin; Tamam, N.; Salah, Hassan; Tahir, Dahlang; Alkhorayef, Mohammed; Sulieman, Abdelmoneim; Bradley, D.A. * (Elsevier, 2023)
Occupational radiation exposure can occur due to various human activities, including the use of radiation in medicine. Occupationally exposed personnel surpassing 7.4 millions, and respresent the biggest single group of employees who are exposed to artificial radiation sources at work. This study compares the occupational radiation dose levels for 145 workers in four different hospitals located in the Aseer region in Saudi Arabia. The occupational exposure was quantified using thermoluminescence dosimeters (TLD-100). The levels of annual occupational exposures in targeted hospitals were calculated and compared with the levels of the international atomic energy agency (IAEA) Safety Standards. An average yearly cumulative dose for the two consecutive years. The average, highest and lowest resulted occupational doses under examination in this work is 1.42, 3.9 mSv and 0.72 for workers in various diagnostic radiology procedures. The resulted annual effective dose were within the IAEA approved yearly dose limit for occupational exposure of workers over 18, which is 20 mSv. Staff should be monitored on a regular basis, according to current practice, because their annual exposure may surpass 15% of the annual effective doses.